2020
DOI: 10.3389/fbioe.2020.594247
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as a Novel Approach to Reverse Osteoporosis: A Review of the Literature

Abstract: Osteoporosis is a chronic disease requiring long-term, sometimes lifelong, management. With the aging population, the prevalence of osteoporosis is increasing, and with it so is the risk of hip fracture and subsequent poor quality of life and higher mortality. Current therapies for osteoporosis have various significant side effects limiting patient compliance and use. Recent evidence has demonstrated the significant role of exosomes in osteoporosis both in vivo and in vitro. In this review, we summarize the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 85 publications
(89 reference statements)
0
27
0
Order By: Relevance
“…Osteoporosis (OP) is a multifactorial skeletal disease with an increased risk of fracture [ 1 ]. With the extension of mean life expectancy and aging, the prevalence of OP is progressively raising [ 2 ]. The prevalence rates of people over 50 and 60 years old were 19.2% and 32% in China according to an epidemiologic survey in 2018 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis (OP) is a multifactorial skeletal disease with an increased risk of fracture [ 1 ]. With the extension of mean life expectancy and aging, the prevalence of OP is progressively raising [ 2 ]. The prevalence rates of people over 50 and 60 years old were 19.2% and 32% in China according to an epidemiologic survey in 2018 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Exo can be safely applied and possesses potent osteogenic abilities, using Exo to reverse OP is promising (Xie X et al. 2020 ). Different studies have shown a relationship between the application of Exo and osteogenic differentiation of MSCs or a relationship with the activity of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miRNAs are increasingly thought to be major regulators of gene expression and control the differentiation and activities of osteoclasts (Xie X et al. 2020 ; Hensley and McAlinden 2021 ). With the aid of bioinformatics prediction and microarray analyses, the PTGS2 gene was identified and found to be downregulated, and miR-101-3p was upregulated in both MOP-treated rats and MOP-Exo.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of EVs has a crucial influence on their biological functions; as transmitters, EVs can activate cell surface receptor binding on target cells through proteins and bioactive lipid ligands, thereby inducing intracellular signaling and regulating the biological activity of the target cells. Besides, EVs can deliver their contents to target cells by fusing with the plasma membrane [ 17 , 32 ]. Figure 1 shows the biogenesis and secretion of EVs and their effects on target cells.…”
Section: The Characteristics Of Extracellular Vesiclesmentioning
confidence: 99%
“…The circulating EVs can maintain systemic immune homeostasis and regulate psychological stress-induced sterile inflammation by transmitting immunomodulatory signals [ 10 ]. Similarly, EVs can regulate the function of osteoblasts and osteoclasts, and consequently have a potential impact on osteoporosis [ 17 ]. Therefore, this review aims to evaluate whether EVs act as mediators of psychosocial stress and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%